Regulation of perforin activation and pre‐synaptic toxicity through C‐terminal glycosylation. (14th August 2017) - House, Imran G; House, Colin M; Brennan, Amelia J; Gilan, Omer; Dawson, Mark A; Whisstock, James C; Law, Ruby HP; Trapani, Joseph A; Voskoboinik, Ilia
Abstract: Perforin is a highly cytotoxic pore‐forming protein essential for immune surveillance by cytotoxic lymphocytes. Prior to delivery to target cells by exocytosis, perforin is stored in acidic secretory granules where it remains functionally inert. However, how cytotoxic lymphocytes remain protected from their own perforin prior to its export to secretory granules, particularly in the Ca 2+ ‐rich endoplasmic reticulum, remains unknown. Here, we show that N‐linked glycosylation of the perforin C‐terminus at Asn549 within the endoplasmic reticulum inhibits oligomerisation of perforin monomers and thus protects the host cell from premature pore formation. Subsequent removal of this glycan occurs through proteolytic processing of the C‐terminus within secretory granules and is imperative for perforin activation prior to secretion. Despite evolutionary conservation of the C‐terminus, we found that processing is carried out by multiple proteases, which we attribute to the unstructured and exposed nature of the region. In sum, our studies reveal a post‐translational regulatory mechanism essential for maintaining perforin in an inactive state until its secretion from the inhibitory acidic environment of the secretory granule. Synopsis: N‐linked glycosylation of the perforin C‐terminus inhibits oligomerisation of perforin monomers, protecting the host cell from premature pore formation. Removal of this glycan in secretory granules through proteolytic processing is imperative for perforin activation. Perforin is synthesised as a non‐functional precursor due to its glycosylation. Carboxy‐terminal N‐glycosylation causes steric hindrance and prevents perforin oligomerisation. Removal of the carboxy‐terminal N‐glycosylation is essential for perforin activation. Despite high conservation, the perforin carboxy‐terminus lacks a protease‐specific consensus. Abstract : N‐linked glycosylation of the perforin C‐terminus inhibits oligomerisation of perforin monomers, protecting the host cell from premature pore formation. Removal of this glycan in secretory granules through proteolytic processing is imperative for perforin activation.